A non-singular analytical technique for reinforced non-circular holes in orthotropic laminate - Pradeep, Mohan; Ramesh Kumar Radha (Zielona Góra: Uniwersytet Zielonogórski)
The present analytical solution for reinforced square hole in an orthotropic infinite plate is derived by completely eliminating stress singularity that depends on the concept of stress ratio. The region of validity of the present analytical solution on reinforcement area is arrived at based on a comparison with the finite element analysis. The present study will also be useful for deriving analytical solution for orthotropic shell with reinforced noncircular holes.
Keywords: power series; stress ratio; non-circular hole